A Health Policy Analysis of the Dottorota Homecare Program - Ni Made Diah Pusparini Pendet (Babali Nursing Research, 2022)
Introduction: Poor health access had initiated the innovation of a homecare program in Makassar. Dottorota Home Care Program is a local program presented to improve the coverage of health care access in Makassar City, contributing to better community health status. This manuscript aimed to provide a health policy analysis of the Dottorota Home Care Program in Makassar City through the policy analysis triangle. Methods: This study enrolled the framework of policy analysis triangle to explore the Dottorota Home Care program as formulated on the Mayor of Makassar Regional Regulation Number 6 of 2016 on Twenty-Four-Hours-Home Visitation Services (Homecare) in Makassar City. Results: The policy content confined the general requirement of aims and principles; scopes; home visits (home care); rights and responsibilities of the health professionals; rights and responsibilities of the patients; coordination and collaboration; guidance and supervision; funding and closing requirement. Legal and non-legal authorities played a role as actors in the policies formulation. The legal parties consist of the Mayor of Makassar, Makassar Local Authorities, Makassar Health Department, Public Health Centers, National Government, and South Sulawesi Regional Government. Hospitals, universities, and the community played the role of non-legal parties in the policy formulation. The context of the policy comprised political and legal, social-cultural, technology development, and economic aspect. The process identified were issue identification, policy arrangement, preparation, implementation, and evaluation. Recommendation: We suggest intensive information dissemination of the program introduction and its procedure to the community.